2010
DOI: 10.1186/1755-8166-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation and implementation of array comparative genomic hybridisation as a first line test in place of postnatal karyotyping for genome imbalance

Abstract: BackgroundSeveral studies have demonstrated that array comparative genomic hybridisation (CGH) for genome-wide imbalance provides a substantial increase in diagnostic yield for patients traditionally referred for karyotyping by G-banded chromosome analysis. The purpose of this study was to demonstrate the feasibility of and strategies for, the use of array CGH in place of karyotyping for genome imbalance, and to report on the results of the implementation of this approach.ResultsFollowing a validation period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…This rapid replacement of karyotype analysis by array CGH testing is fuelled by the greatly increased resolution of array CGH, and the objectivity and ease of the analytical process. Various different array CGH platforms are commercially available; most diagnostic laboratories are in agreement that platforms comprising oligonucleotide probes have better resolution and provide more accurate and reproducible results than those comprising bacterial artificial chromosome clones ( Ylstra et al 2006;Ahn et al 2010). Oligonucleotide array platforms are available in a number of formats, with different probe densities across the genome.…”
Section: Copy Number Variations: Molecular Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…This rapid replacement of karyotype analysis by array CGH testing is fuelled by the greatly increased resolution of array CGH, and the objectivity and ease of the analytical process. Various different array CGH platforms are commercially available; most diagnostic laboratories are in agreement that platforms comprising oligonucleotide probes have better resolution and provide more accurate and reproducible results than those comprising bacterial artificial chromosome clones ( Ylstra et al 2006;Ahn et al 2010). Oligonucleotide array platforms are available in a number of formats, with different probe densities across the genome.…”
Section: Copy Number Variations: Molecular Diagnosticsmentioning
confidence: 99%
“…In addition, in shorter chromosome preparations, such as those typically obtained from cell lines, only abnormalities of whole chromosome copy number and very large imbalances can confidently be assigned (figure 3). Advances in molecular cytogenetic technologies have recently led to the introduction of array comparative genomic hybridization (CGH) as either an add-on test following karyotype analysis for the detection of chromosome imbalance (Edelmann & Hirschhorn 2009) or, in an increasing number of centres, as a first-line test (Ahn et al 2010). This rapid replacement of karyotype analysis by array CGH testing is fuelled by the greatly increased resolution of array CGH, and the objectivity and ease of the analytical process.…”
Section: Copy Number Variations: Molecular Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, microarray analyses provide accurate diagnosis in approximately twice as many cases as classical karyotyping and fluorescent in situ hybridization (Gijsbers et al, 2009;Hochstenbach et al, 2009;Ahn et al, 2010;Miller et al, 2010). In recent years, approximately 15-20% of ID cases are caused by submicroscopic CNVs (Zahir and Friedman, 2007;Gijsbers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the study of Ou et al clearly showed that oligo-based arrays offered a valid alternative for focused BAc arrays, furthermore without the need for dye-swap experiment (10). in another study 42 patients were tested on both BAc and oligo array platforms where discordance was found in six cases -BAc arrays failed to detect the imbalances (1). the genome-wide analysis for CNVs in a set of 19 patient probes BAC platforms identified 71 deletions and 74 amplifications, whereas the oligo platform detected 314 deletions and 209 amplifications with median lengths of 12 Mbp and 3.5 Mbp respectively (22).…”
Section: Resultsmentioning
confidence: 99%